Identification of a novel mechanism of action of fingolimod (FTY720) on human effector T cell function through TCF-1 upregulation. Issue 1 (December 2015) - Mazzola, Maria; Raheja, Radhika; Murugaiyan, Gopal; Rajabi, Hasan; Kumar, Deepak; Pertel, Thomas; Regev, Keren; Griffin, Russell; Aly, Lilian; Kivisakk, Pia; Nejad, Parham; Patel, Bonny; et al.
Abstract Background Fingolimod (FTY720), the first oral treatment for multiple sclerosis (MS), blocks immune cell trafficking and prevents disease relapses by downregulation of sphingosine-1-phosphate receptor. We determined the effect of FTY720 on human T cell activation and effector function. Methods T cells from MS patients and healthy controls were isolated to measure gene expression profiles in the presence or absence of FTY720 using nanostring and quantitative real-time polymerase chain reaction (qPCR). Cytokine protein expression was measured using luminex assay and flow cytometry analysis. Lentivirus vector carrying short hairpin RNA (shRNA) was used to knock down the expression of specific genes in CD4+ T cells. Chromatin immunoprecipitation was performed to assess T cell factor 1 (TCF-1) binding to promoter regions. Luciferase assays were performed to test the direct regulation of interferon gamma (IFN-γ) and granzyme B (GZMB) by TCF-1. Western blot analysis was used to assess the phosphorylation status of Akt and GSK3β. Results We showed that FTY720 treatment not only affects T cell trafficking but also T cell activation. Patients treated with FTY720 showed a significant reduction in circulating CD4 T cells. Activation of T cells in presence of FTY720 showed a less inflammatory phenotype with reduced production of IFN-γ and GZMB. This decreased effector phenotype of FTY720-treated T cells was dependent on the upregulation of TCF-1. FTY720-induced TCF-1 downregulated the pathogenic cytokines IFN-γ and GZMB by binding to their promoter/enhancer regions and mediating epigenetic modifications. Furthermore, we observed that TCF-1 expression was lower in T cells from multiple sclerosis patients than in those from healthy individuals, and FTY720 treatment increased TCF-1 expression in multiple sclerosis patients. Conclusions These results reveal a previously unknown mechanism of the effect of FTY720 on human CD4+ T cell modulation in multiple sclerosis and demonstrate the role of TCF-1 in human T cell activation and effector function.